2021
DOI: 10.1177/08982643211043319
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Care and Outcomes Among a Diverse Group of Long-Term Care Residents With Alzheimer’s Disease and Related Dementias

Abstract: Objectives This article assessed whether disparities among ADRD Medicare beneficiaries existed in five different long-stay quality measures. Methods: We linked individual-level data and facility-level characteristics. The main quality outcomes included whether residents: 1) were assessed/appropriately given the seasonal influenza vaccine; 2) received an antipsychotic medication; 3) experienced one/more falls with major injury; 4) were physically restrained; and 5) lost too much weight. Results: In 2016, there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 49 publications
(64 reference statements)
0
11
0
Order By: Relevance
“…55 Anti-depressant use was also higher in NHW compared to other racial/ethnic groups. 56 Finally, one study found higher rates of anti-psychotic medication (i.e., "low value care") in Hispanic Americans and NHW compared to the "other race" category. 57 Two studies reported on potentially inappropriate medication use-"drugs that should generally be avoided because they are ineffective or pose an unnecessarily high risk for older adults, and drugs that are appropriate to use in older persons only at certain doses, frequencies, or duration of therapies."…”
Section: Total Sample (N) Racial/ethnic Populations Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…55 Anti-depressant use was also higher in NHW compared to other racial/ethnic groups. 56 Finally, one study found higher rates of anti-psychotic medication (i.e., "low value care") in Hispanic Americans and NHW compared to the "other race" category. 57 Two studies reported on potentially inappropriate medication use-"drugs that should generally be avoided because they are ineffective or pose an unnecessarily high risk for older adults, and drugs that are appropriate to use in older persons only at certain doses, frequencies, or duration of therapies."…”
Section: Total Sample (N) Racial/ethnic Populations Resultsmentioning
confidence: 99%
“…Six studies reported on use of psychotropic medications across racial/ethnic groups 52–57 . Three of these studies found higher use of anti‐psychotic medication in Hispanic Americans compared to NHW 52–54 adults while one study reported higher use in NHW compared to Hispanic Americans 55 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, little work has examined racial/ethnic disparities in QOL domains measured by validated instruments studied in AD/ADRD populations (Qin et al, 2021). While previous studies have found racial/ethnic disparities in NH QoC outcomes for people with AD/ADRD (Rivera-Hernandez et al, 2019, 2022), this is the first study to use multiple sources of data to examine racial/ethnic disparities in QoL for NH residents with AD/ADRD, giving voice to a vulnerable population’s experience.…”
Section: Discussionmentioning
confidence: 97%
“…Importantly, minoritized persons have poorer access to NHs with specialized dementia care units, which may be associated with better outcomes (Rivera-Hernandez et al, 2019). Finally, Rivera-Hernandez et al (2019, 2022) examined differences in NH QoC among Medicare beneficiaries (Rivera-Hernandez et al, 2019, 2022). They found that a larger share of Hispanic Medicare residents who are admitted to NHs have AD/ADRD compared with Black and White beneficiaries.…”
Section: Background and Contextmentioning
confidence: 99%